Understanding team coordination in doubles table tennis: Joint analysis of first- and third-person data - Poizat, G.; Bourbousson, J.; Saury, J.; Sève, C. (Psychology of Sport and Exercise, 2012)
Objectives: This study sought to determine whether combining first- and third-person methodologies would provide insight into team coordination. Design and methods: We studied the activity of a table tennis doubles team during an official match. We collected and processed the verbal data according to a procedure defined for course-of-experience analysis, but we also included a video-based field study of the partners' interactions during the breaks between points. We then conducted a joint analysis of the two players' lived experience and behaviors during these short breaks. Results: The results showed both the difficulties and the empirical richness of this approach. For example, the joint analysis of first- and third-person data on doubles table tennis revealed how the players' behaviors during the short breaks between points had a key role in shaping the understanding shared by the two partners. Conclusions: The combination of first- and third-person data seems to be a promising approach for improving our understanding of the coordination processes in sports teams. In our study, the joint analysis of these data enabled us to describe in great detail how the respective behaviors of the partners contributed to the dynamics of constructing/deconstructing shared understanding between them.